ENTERPRISE ARCHITECTURE PLANNING FOR DIGITAL TRANSFORMATION AND EDUCATIONAL GOVERNANCE IN ISLAMIC SECONDARY SCHOOLS: A CASE STUDY OF MTS RADEN INTAN GADINGREJO - Rosdiana Listiawati; Muhamad Muslihudin; Ferry Susanto (JECE (Journal of Ethics and Character Education), 2025)
The digital system in the era of digitalization is developing rapidly, so it requires the Management of MT Raden Intan Gadingrejo to meet functional needs in the fields of data, applications, and technology. The role of technology is crucial in providing information to support decision-making. Therefore, it is necessary to design an information system that allows users to access data and information effectively. Enterprise Architecture Planning (EAP) is a method of planning your entire information architecture. The EAP phase includes data architecture, application architecture, technology architecture, and implementation design. In this study, we used use case diagrams, activity diagrams, and entity relationship diagrams as implementation support tools. MTs Raden Intan Gadingrejo's research produced a strategic blueprint in the form of a mobile website-based information system. The purpose of this system is to improve the quality of services in madrassas by allowing users to access information easily even when they are not there. Only with software and an online connection, users can access information easily. This design is expected to be a reference for improving services in schools and providing effective digital solutions.